From Virality to Veracity: Understanding User Engagement and Information Accuracy in Breaking Events - Tamika Taylor (Journal of Linguistics and Communication Studies, 2024)
This research explores the intricate dynamics of user engagement, information virality, and accuracy during breaking events within the timeframe of 2017-2022. Employing a mixed-methods approach, we analyze user behaviors on social media platforms, exploring the quantitative metrics of likes, shares, and comments, while also unraveling the qualitative dimensions through participant interviews. The study uncovers a nuanced spectrum of user engagement, ranging from information-seeking tendencies to profound emotional responses, unveiling the complex interplay that shapes digital interactions during critical moments. The investigation into information virality reveals the significant impact of emotional appeal, novelty, and alignment with societal concerns on the dissemination of information. A meticulous dissection of network dynamics elucidates the influential roles played by influencers and the intricate dance of user sharing patterns. Simultaneously, the scrutiny of information accuracy establishes a positive correlation between accurate information and trust in traditional sources, unveiling the multifaceted consequences of misinformation. In the broader context of existing literature, our findings align with the growing body of research emphasizing the pivotal role of social media in shaping narratives during breaking events. This study contributes to a deeper understanding of the challenges posed by the digital landscape and highlights the need for adaptive strategies that balance information dissemination and accuracy.